IMPLEMENTATION OF THE AMO MODEL IN IMPROVING EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT IN THE BANKING SECTOR IN JAKARTA - Dewi Kurniawati; Chaerani Nisa; Tia Ichwani; Sri Widyastuti; Damara Azzalia Narda (INQUISITIVE : International Journal of Economic, 2026)
This study aims to analyze the implementation of the Ability–Motivation–Opportunity (AMO) model in improving employee performance through employee engagement in the banking sector in Jakarta. A quantitative approach with an explanatory research design was employed. Data were collected through a five-point Likert scale questionnaire administered to 160 banking employees selected using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS 4.0. The results indicate that ability, motivation, and opportunity have a positive and significant effect on employee engagement. Furthermore, employee engagement has a positive and significant effect on employee performance. The mediation analysis reveals that employee engagement significantly mediates the relationship between ability and motivation with employee performance. However, employee engagement does not mediate the relationship between opportunity and employee performance. The coefficient of determination shows that the model has moderate explanatory power, where AMO variables explain 48.7% of the variance in employee engagement, while the combination of AMO and employee engagement explains 60.7% of the variance in employee performance. These findings suggest that improving employee performance in the banking sector is not only influenced by competence and motivation but also by the level of employee engagement within the organization. This study provides practical implications for banking organizations to enhance employee performance through the strengthening of AMO-based human resource management practices and the continuous improvement of employee engagement.